WORD SQUARE DAN TEKA TEKI SILANG UNTUK MENINGKATKAN AKTIVITAS SISWA KELAS XII MIPA MATERI MEDAN MAGNET - SRI WAHYUNINGSIH (SCIENCE : Jurnal Inovasi Pendidikan Matematika dan IPA, 2022)
This study aims to increase the activity of class XII MIPA students at SMA Negeri Rembang. This classroom action research applies two cycles, with each cycle two meetings. Word squares are used to apply conceptual understanding while crosswords are used to apply calculation questions. The results of this study are visual activity, in the aspect of reading questions and students looking for references, in cycle 1 there are 1 to 8 students so it has a value of 1.67, meaning that the assessment criteria are less active. Oral activity, in terms of the number of students who submitted answers in cycle 1 has a value of 1.67, meaning that the assessment criteria are less active. Listening activity has a value of 1.5, meaning that the assessment criteria are less active. Likewise with writing activities and emotional activities. As for motor activity, namely conducting experiments, the value is good. In cycle 2, visual activities, oral activities, listening activities, writing activities and emotional activities, the students' activities increased so that they were quite active. Meanwhile, in motor activity and emotional activity, the number of students doing the experiment increased with joy. This classroom action research resulted in an increase in activity until the value was quite active. ABSTRAKPenelitian ini bertujuan untuk meningkatkan aktivitas siswa kelas XII MIPA SMA Negeri Rembang. Penelitian tindakan kelas ini menerapkan dua siklus, dengan tiap siklus dua pertemuan. Word square dipakai untuk penerapan pemahaman konsep sedangkan teka-teki silang untuk menerapkan soal hitungan. Hasil penelitian ini Aktivitas visual, pada aspek membaca soal pertanyaan dan siswa yang mencari referensi, di siklus 1 ada 1 sampai 8 siswa sehingga memiliki nilai 1,67, artinya kriteria penilaiannya adalah kurang aktif. Aktivitas Oral, pada aspek banyaknya siswa yang mengajukan jawaban pada siklus 1 memiliki nilai 1,67 artinya kriteria penilaiannya kurang aktif. Aktivitas Listening bernilai 1,5 artinya ktiteria penilaiannya kurang aktif. Demikian juga dengan aktivitas writing dan aktivitas emosional. Sedangkan untuk aktivitas motorik yaitu melakukan percobaan nilainya baik. Pada siklus ke 2, aktivitas visual, aktivitas Oral, Aktivitas Listening, aktivitas writing dan aktivitas emosional, siswa yang beraktivitas semakin bertambah sehingga cukup aktif. Sedangkan di aktivitas motorik dan aktivitas emosional, dengan rasa gembira sejumlah siswa yang melakukan percobaan bertambah. Penelitian tindakan kelas ini menghasilkan peningkatan aktivitas sampai nilai cukup  aktif.